AN ANALYSIS OF FILLERS USED BY BILL GATES IN THE DAVID RUBENSTEIN SHOW - Fadil Juliano; Imeldayanti Nehe; Nurma Dhona Handayani (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
Fillers are speech markers that are used by speakers to indicate when they are thinking and/or hesitating during their speech. The theory of spoken discourse states that a speaker may use various prefabricated fillers in his or her utterances, including err, ehm, well, I think, you know, if you see, what I mean, and so on Yule (1983) Furthermore, Clark & Tree (2002) stated Fillers provided a communicative function by having a position in the speaker's lexicon. The purpose of this research is to investigate the types of fillers and function filler used by the Microsoft Co-Founder Bill Gates in the David Rubenstein Show which as the subject of this research. This research was applied descriptive qualitative method. By using the theory of Stenstrom (1994) supported by Rose, (1998). The result of this research, the researcher found two types of filler were used in the show namely, lexicalized and unlexicalized fillers. Base on the analysis of the researcher, found the types of fillers most frequently used were unlexicalized which were used 37 times, and lexicalized fillers which were used 34 times, From the total number of each type of fillers, the most frequently used were you know for 21 times, followed by ee occurred for 19 times. Then, filler eer with the number of occurrences 15 times. The last is filler Well were frequent used 9 times in the utterance. Furthermore, the most function frequent used in the interview were mark of hesitating 38 times and the empathizing used 23 times and followed by well used 9 times.